The gastroprotective effects of arrowroot tuber starch (Maranta arundinacea L.) on ethanol-induced gastric damages in rats - Vella Lailli; Moch Saiful Bachri; Wahyu Widyaningsih (Universitas Ahmad Dahlan, 2020)
Empirically, arrowroot tubers (Maranta arundinacea L.) have been widely used in the treatment of gastric ulcers. They are known to contain carbohydrates and flavonoids that play a role in reducing inflammation. This study sought to identify the gastroprotective effects of arrowroot tuber starch (Maranta arundinacea L.) on the ulcer index, % protection ratio, and the histopathological image of Wistar rat models of gastric ulcers. The test animals were divided into six groups. Group I was given free access to food and water (normal control), while Group II was given ethanol without treatment (negative control). Groups III, IV, and V were treated with arrowroot tuber starch at the doses of 125, 250, and 500 mg/kg BW, respectively. Group VI was given sucralfate at the dose of 400 mg/kg BW (positive control). All treatments were administered orally for 14 days and followed by 24 hours of fasting. On Day 15, all groups, except for the normal control, were given 96% ethanol orally at the dose of 1 ml/200gr BW. After one hour, they were dissected, and their stomach was removed for further analyses. The results showed that the administrations of arrowroot tuber starch at 125, 250, and 500 mg/kg BW produced ulcer indices of 2, 1.25, and 1.5, respectively, smaller than the negative control (4.25), and % protection ratios higher than the positive control. The histopathological imaging showed that the stomach of rats receiving arrowroot tuber starch at 250 mg/kg BW presented no pathological changes. Based on these findings, the arrowroot tuber starch is proven to have the ability as a gastroprotective agent.